(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The article examines students’ independent work as a crucial element in the training of future doctors, emphasizing its role in an individual approach to learning. SR promotes the development of key professional skills: clinical reasoning, self-study, the ability to apply knowledge in practice, and conduct scientific research. SR is divided into three main forms: educational and cognitive, scientific research, and social. The primary focus is on the educational aspect, which includes self-study, work with literature, and participation in practical classes. Students’ research consists of collecting material, analyzing it, participating in scientific conferences and presentations, which develops research skills. Three levels of student preparation must be taken into account: first-year students, mid-year students, and graduates. However, effectiveness is determined not by the course itself, but by the skills formed knowledge and skills. The instructor prepares assignments, provides consultations, and motivates students for their work. Topics for the course "Propaedeutics of Internal Medicine" range from analyzing laboratory and instrumental data to studying the characteristics of disease progression.